Inadequate Household Environmental Sanitation Is a Significant Determinant of Stunting Among Toddlers - Jayadi, Hurip; Mawaddah, Zulfi Hanifatul; Indraswati, Denok (FORIKES, 2026)
Stunting is a serious public health problem in Indonesia and reflects chronic malnutrition as well as poor environmental conditions, particularly inadequate sanitation. In the working area of Mejuwet Health Center, Bojonegoro Regency, the prevalence of stunting in 2023 remained above the WHO threshold for high prevalence. This study aimed to analyze the relationship between environmental sanitation conditions and the incidence of stunting among toddlers aged 24–59 months in the area. This research employed a quantitative method with an observational analytic approach and a cross-sectional design. The independent variables consisted of environmental sanitation indicators, while the dependent variable was stunting incidence. The sample included 180 toddlers divided into two groups: 90 cases (stunted toddlers) and 90 controls (non-stunted toddlers). Data were collected through questionnaires, direct observation, and secondary data from the health center. Statistical analysis was conducted using chi-square tests and logistic regression. The Chi-square results demonstrated significant associations between stunting and all environmental sanitation indicators: ownership of healthy latrines (p=0.000), availability of clean water facilities (p=0.001), solid waste disposal facilities (p=0.000), and wastewater disposal facilities (p=0.007). Overall environmental sanitation conditions were significantly associated with stunting (p=0.005). The most dominant variables influencing stunting were healthy latrine ownership and solid waste disposal facilities. In conclusion, all environmental sanitation indicators show significant relationships with stunting among toddlers. Integrated water, sanitation, and hygiene (WASH) interventions involving improvements in basic infrastructure and promotion of hygienic behavior are necessary to reduce stunting prevalence and create a healthy environment that supports optimal child growth and development.Keywords: stunting; environmental sanitation; toddlers